1986
DOI: 10.1213/00000539-198609000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Ketamine for Control of Postoperative Pain

Abstract: ANESTll ANALG 990 1986,65.988-92 LETTERS TO THE EDITOR I 2. 3. 4 3. 6 . Isla:. j, Astorga J, Laredo M Epidural ketamine for control of postoperative pain. Anesth Analg 1985;64:1161-2. Logas WG, Faber LP, El-Ganzouri A, Ivankovich AD. A prospective double-blind study of continuous epidural analgesia for thoracotomy patients. Anesthe\idogy 1984;64:A222. Cullen ML, Starren ED, El-Ganzouri A, Logas WG, Ivankovich AD, Economous SG. Continous epidural infusion for analgesia after major abdominal operations: a random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In fact after the epidural application of this dosage the authors did not note the onset of a motor block or of systemic effects. Subsequently, Brock-Utne et al [82], following their initial enthusiasm on ketamine by epidural means [62] concluded that not even epidural doses of 50 mg are able to provide an adequate postoperative analgesic response.…”
Section: Epidural Administrationmentioning
confidence: 99%
“…In fact after the epidural application of this dosage the authors did not note the onset of a motor block or of systemic effects. Subsequently, Brock-Utne et al [82], following their initial enthusiasm on ketamine by epidural means [62] concluded that not even epidural doses of 50 mg are able to provide an adequate postoperative analgesic response.…”
Section: Epidural Administrationmentioning
confidence: 99%